Cost-effective methods for accurate determination of sea level rise vulnerability: a Solomon Islands example - Albert, S.; Abernethy, K.A.; Gibbes B; Grinham A; Tooler N; Aswani S (American Meteorological Society, 2013)
For millions of people living along the coastal fringe, sea level rise is perhaps the greatest threat to livelihoods over the coming century. With the refinement and downscaling of global climate models and increasing availability of airborne-lidar-based inundation models, it is possible to predict and quantify these threats with reasonable accuracy where such information is available. For less developed countries, especially small island states, access to high-resolution digital elevation models (DEMs) derived from lidar is limited. The only freely available DEMs that could be used for inundation modeling by these nations are those based on data from the Shuttle Radar Topography Mission (SRTM). These data, with a horizontal resolution of ’90m and a vertical accuracy of 65–10 m, are generally unsuitable for local-scale planning and adaption projects. To address this disparity, low-cost ground-based techniques were tested and applied to accurately determine coastal topography in the Solomon Islands. This method had a significantly improved vertical accuracy (62 cm) and was readily learned by local community members, who were able to independently map and determine the vulnerability of their costal community to inundation from sea level rise. For areas where lidar is not economically viable, this method is intended to provide an important balance of cost, simplicity, accuracy, and local participation that can assist remote coastal communities with coastal planning decisions. The method can enhance local capacity and arguably promotes more meaningful local engagement in sea level rise planning and adaptation activities.